Partial pressure (or fugacity) of carbon dioxide, dissolved inorganic carbon, pH, alkalinity, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from DISCOVERY in the English Channel, Inner Sea - West Coast Scotland and others from 2011-06-06 to 2011-07-09 (NCEI Accession 0157465) ... - Bakker, Dorothee C. E.; Kitidis, Vassilis; Rerolle, Victoire; Lee, Gareth A.; Palmer, Matthew R.; Young, Jeremy; Stinchcombe, Mark; Tyrrell, Toby (NOAA National Centers for Environmental Information, 2016)
This dataset includes Surface underway, chemical, meteorological and physical data collected from DISCOVERY in the English Channel, Inner Sea - West Coast Scotland, Irish Sea and St. George's Channel, North Atlantic Ocean, North Sea and Skagerrak from 2011-06-06 to 2011-07-09. These data include AIR-SEA DIFFERENCE - PARTIAL PRESSURE (OR FUGACITY) OF CARBON DIOXIDE, BAROMETRIC PRESSURE, DISSOLVED INORGANIC CARBON (DIC), Partial pressure (or fugacity) of carbon dioxide - atmosphere, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY, SEA SURFACE TEMPERATURE, TOTAL ALKALINITY (TA) and pH. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and thermosalinographs. These data were collected by Vassilis Kitidis of Plymouth Marine Laboratory, Dorothee C. E. Bakker of University of East Anglia; School of Environmental Sciences, and Victoire Rerolle of University of Southampton, UK as ...